Hydrogels Generated from Cyclic Poly(2‐Oxazoline)s Display Unique Swelling and Mechanical Properties. Issue 7 (8th April 2021) - Trachsel, Lucca; Romio, Matteo; Zenobi‐Wong, Marcy; Benetti, Edmondo M.
Abstract : Front Cover : The cover image depicts a hydrogel fabricated from cyclic poly(2‐alkyl‐2‐oxazoline)s crosslinked via thiol‐Michael reaction. In the background, the composition of the crosslinked network is provided. This work is featured in article number 2000658 by Edmondo M. Benetti and co‐workers.